2021
DOI: 10.5530/ijper.55.2s.117
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Caffeic Acid in Cognitive Dysfunction and Oxidative Stress Induced by Colchicine in Rats

Abstract: Purpose: Alzheimer's is a disease affecting mostly the Older population leading to the deterioration of cognitive capabilities. The protective effect of Caffeic acid in Colchicineinduced dementia was evaluated in the current study. Materials and Methods: Colchicine was administered intracerebroventricularly (ICV) to the lateral ventricle of the brain (at the coordinates 0.8 mm posterior to bregma, 1.8 mm lateral to the sagittal suture, 3.6 mm below the cortical surface) using robotic stereotaxic apparatus that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Frontiers in Pharmacology frontiersin.org neuroinflammation (Zhang et al, 2019;Colonnello et al, 2020;Raviteja et al, 2021;Salau et al, 2021). Caffeic acid exhibited protective mechanisms through Nrf2 and skn-1 pathways against 6-hydroxydopamine and quinolinic acid, a neurotoxicity model that led to the increase of ROS and excitotoxicity (Colonnello et al, 2020).…”
Section: Subedi Et Al (2017)mentioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Pharmacology frontiersin.org neuroinflammation (Zhang et al, 2019;Colonnello et al, 2020;Raviteja et al, 2021;Salau et al, 2021). Caffeic acid exhibited protective mechanisms through Nrf2 and skn-1 pathways against 6-hydroxydopamine and quinolinic acid, a neurotoxicity model that led to the increase of ROS and excitotoxicity (Colonnello et al, 2020).…”
Section: Subedi Et Al (2017)mentioning
confidence: 99%
“…Caffeic acid was known to possess protective properties such as neuroprotective and anti-inflammatory activities ( Colonnello et al, 2020 ). According to recent studies, caffeic acid demonstrated neuroprotective effects by regulating oxidative stress and neuroinflammation ( Zhang et al, 2019 ; Colonnello et al, 2020 ; Raviteja et al, 2021 ; Salau et al, 2021 ). Caffeic acid exhibited protective mechanisms through Nrf2 and skn-1 pathways against 6-hydroxydopamine and quinolinic acid, a neurotoxicity model that led to the increase of ROS and excitotoxicity ( Colonnello et al, 2020 ).…”
Section: Neuroprotective and Anti-neuroinflammatory Effects Of ...mentioning
confidence: 99%
“…Bregma was used as a reference point for the software. 5µL of Arti cial cerebrospinal uid (ACSF) (composition:147mM NaCl, 2.9mM KCl, 1.6mM MgCl 2 , 1.7mM CaCl2, and 2.2mM dextrose) administration to sham control group and STZ (3mg/kg, 5µl) administration was done bilaterally at the coordinates 0.8 mm AP,1.8 mm ML, 3.6 mm DV (Raviteja et al 2021) to all other group of rats using Hamilton micro syringe at infusion rate of 1µl/min. After completion of the infusion, it was ensured that the syringe is not disturbed for at least 2 min to prevent the back ow.…”
Section: Experimental Design Intracerebroventricular (Icv) Injection ...mentioning
confidence: 99%
“…Lipid peroxidation (LPO) level in the brain sample was measured as per the method described earlier. (Kumar et al 2016;Raviteja et al 2021). Equal volume of brain homogenate (100 µl each) and TBA-TCL reagent were mixed, heated in water bath maintained at 90 for 10 mins.…”
Section: Estimation Of Lipid Peroxidationmentioning
confidence: 99%
See 1 more Smart Citation